Radiological evaluation of odontogenic keratocysts in patients with nevoid basal cell carcinoma syndrome: A review - Gürkan Ünsal; Marco Cicciù; Rand Ayman Ahmad Saleh; Mohammed Riyadh Ali Hammamy; Anwer Amer Kadri; Bilge Kuran; Giuseppe Minervini (Elsevier, 2023)
Background: Nevoid Basal Cell Carcinoma Syndrome (NBCCS) is an autosomal dominant syndrome that has various expressions in each patient. Generally; NBCCS is followed by multiple nevoid basal cell carcinoma of the skin, orbital anomalies, skeletal anomalies, central nervous system anomalies and multiple odontogenic keratocysts (OK). NBCCS is usually diagnosed between the ages of 5-30 years, with multiple basal cell carcinomas of the skin and OKs in the jaws as the initial findings. The purpose of this paper is to describe and compare the radiographic findings of the OKs in NBCCS patients in the literature with additional cases. Materials and Methods: In this study, we evaluated the OKs of the patients with NBCCS in PubMed Database with 5 additional cases from our database. A total of 305 articles were found and the articles in English with full-text access were evaluated. Results: Despite all limitations for a fair discussion; we would like to state that among 59 cases that specified whether a 3D or 2D imaging modality was used, 29 cases were only interpreted with 2D data which should be avoided in OK evaluation. Discussion: According to the World Health Organization's Classification of Head and Neck Tumours Book which was published in 2017, OKs in NBCCS has a higher chance to have small satellite cystic lesions which increase their recurrence possibility post-operatively, thus, a thorough clinical and 3D radiographic evaluation should be performed both to NBCCS patients and non-syndromic OK patients to avoid any recurrence. Conclusion: High recurrence rates of OKs should be reminded all the time. Radiographic examinations with 3D imaging modalities should be done in patients with NBCCS in order to provide a concise diagnosis and optimum treatment.